Effects of Multicomponent Fall-Prevention Interventions among Inpatients in General Wards: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yun-Hee Kim; Nam Young Kim; Seang Ryu (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to evaluate the effectiveness of multicomponent fall-prevention interventions, defined as interventions comprising two or more distinct components, in reducing falls among patients admitted to general wards. Methods: Cochrane CENTRAL, MEDLINE, EMBASE, and CINAHL were systematically searched from inception to November 20, 2025. Randomized controlled trials (RCTs) that evaluated multicomponent fall-prevention interventions in adults aged ≥19 years admitted to general wards were included. The primary outcome was fall incidence, and usual care served as the comparator. Meta-analysis was performed using Review Manager to estimate risk ratios (RR) with 95% confidence intervals (CI). Results: This systematic review included 10 RCTs: three conducted in acute wards and seven in subacute wards. A total of 39,084 patients were assigned to intervention groups and 38,971 to control groups. In the meta-analysis of nine studies, multicomponent interventions were associated with a lower risk of falls (RR=0.78; 95% CI: 0.62~0.96). However, heterogeneity was substantial (I2=91%), and the pooled effect should therefore be interpreted with caution. Subgroup analyses suggested a reduction in falls in subacute wards (RR=0.73; 95% CI: 0.58~0.91), whereas no clear effect was observed in acute wards (RR=0.96; 95% CI: 0.71~1.31), indicating setting-related variability. Conclusion: Multicomponent fall-prevention interventions based on patient fall-risk factors were associated with reduced fall risk among inpatients in subacute wards. These findings suggest that multicomponent interventions incorporating individual patient characteristics and fall-risk factors may be useful for preventing falls in hospitalized patients.